STUDY OF PENAL POLICY ON CHEMICAL CASTRATION SANCTION ON CHILD SEXUAL CRIMES CASES IN INDONESIA - Krismiyarsi, Krismiyarsi (IJCLS (Indonesian Journal of Criminal Law Studies), 2018)
In Article 28 B paragraph (2) of the Constitution of the Republic of Indonesia, it is stated that the State guarantees the rights of children to survival, to grow and develop and to protect them from violence and discrimination. Along with the rapid flow of globalization and the negative impact of the development of information technology and telecommunications, sexual violence against children is increasing. The Indonesian Child Protection Commission (KPAI), stated that in 2015 there were 218 cases, in 2016 there were 120 cases, and in 2017 there were 116 cases. To address the phenomenon of sexual violence against children, the President of Indonesia issued a Government Regulation in Lieu of Law No. 17 of 2016, which was subsequently upgraded to Law namely Law No. 17 of 2016 concerning Stipulation of Government Regulation in lieu of Law No. 1 of 2016 concerning the second Amendment to Law No. 23 of 2002 concerning Child Protection becomes Law. The contents of criminal offenses against perpetrators of criminal acts of sexual violence against children can be subject to additional criminal sanctions in the form of announcing the identity of the perpetrators, and can be subjected to acts of chemical castration accompanied by rehabilitation and installation of electronic detectors. The basic consideration for the issuance of this Perppu is to minimize sexual crimes, give a deterrent effect to perpetrators of sexual crimes and prevent any intention for anyone to commit sexual crimes. However, the issuance of this Perppu invites pros and cons of how to implement it, considering that until now there has been no further Government Regulation regulating, especially the Indonesian Medical Association has refused to do chemical castration. This paper wants to explore the existence of the Perppu seen from the study of criminal law politics.